PENGEMBANGAN APLIKASI TEMPAT PENGOLAHAN SAMPAH BERBASIS ANDROID MENGGUNAKAN MODEL EXTREME PROGRAMMING DAN BLACK BOX TESTING - Lampung, Pramayota Fane'a; Pratama, I Putu Agus Eka (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
The closure of the TPA, which had been operating since 1990, forced Gunaksa Village to have its own TPST or Local Waste Processing Site (TOSS) as a waste processing site. The Klungkung regency government also requires each village to process household waste independently. This policy obliges Gunaksa Village to have its own (TOSS) as a waste processing site. According to Law No. 18 of 2008 concerning waste management, it is necessary to change the pattern of waste management which is based on reducing and handling waste. The output of this research is in the form of a local waste management application that can help TOSS in Gunaksa Village, Klungkung Regency which is expected to be able to integrate the management of each division and level so that it runs effectively and efficiently. This application is intended as a recording system in the management of waste banks. Research will be conducted using the methodextreme programming. The system will be designed using the Unified Modeling Language (UML). System testing will use the Black Box method. The results of the black box test state that the input and output of the Gunaksa Bank Garbage Application (GUNABANGSA) are appropriate.